2017
DOI: 10.1177/0018578717737431
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spine Surgeries and Medication Usage During Hospital Stay: One-Center Perspective

Abstract: Pain after spine surgery is usually managed with opioid and nonopioids. The rate of lumbar spine surgeries (LSS) is rising, but current practices on LSS are not known. A current trend in LSS and medication usage by age group is needed to gain a better understanding of how LSS and its pain management vary by age. The aim of this study was to report current practices of LSS of discectomy, laminectomy, and fusion in patients aged 18 and older and to gain an understanding of medication use for management of LSS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A previous study has shown that 72% of people who underwent LSS were older than 45 years. 9 The outcomes of LSS, however, are not consistent and significantly vary in both the short-and long-term. 10 We have previously shown that standard pain treatment during the average 3-day hospital stay 11,12 following LSS includes the use of opioid analgesics, and about 97.7% of post LSS patients were treated with opioids alone or with multimodal approaches including opioids.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 4 more Smart Citations
“…A previous study has shown that 72% of people who underwent LSS were older than 45 years. 9 The outcomes of LSS, however, are not consistent and significantly vary in both the short-and long-term. 10 We have previously shown that standard pain treatment during the average 3-day hospital stay 11,12 following LSS includes the use of opioid analgesics, and about 97.7% of post LSS patients were treated with opioids alone or with multimodal approaches including opioids.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…10 We have previously shown that standard pain treatment during the average 3-day hospital stay 11,12 following LSS includes the use of opioid analgesics, and about 97.7% of post LSS patients were treated with opioids alone or with multimodal approaches including opioids. 9 A multimodal analgesic approach has been shown to accelerate patients' recovery and early mobility following peripheral/spinal surgeries. [13][14][15][16][17] However, post-operative pain is primarily managed by increasing the opioid dose, specifically if patients may require intravenous analgesia.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 3 more Smart Citations